Efficacy and safety of once‐daily insulin degludec/insulin aspart compared with once‐daily insulin glargine in participants with Type 2 diabetes: a randomized, treat‐to‐target study. Issue 2 (28th July 2016) - Kumar, S.; Jang, H. C.; Demirağ, N. G.; Skjøth, T. V.; Endahl, L.; Bode, B.
Abstract: Aims: To investigate, in a 26‐week, open‐label, randomized, treat‐to‐target trial, the efficacy and safety of insulin degludec/insulin aspart (IDegAsp) once daily vs insulin glargine (IGlar) once daily in adults with Type 2 diabetes, inadequately controlled on basal insulin. Methods: Participants were randomized (1:1) to IDegAsp once daily or IGlar once daily in combination with existing oral antidiabetic drugs. IDegAsp once daily was administered with the main evening meal or the largest meal of the day (agreed at baseline); dosing time was maintained throughout the trial. Participants titrated their insulin dose weekly to a mean pre‐breakfast self‐measured plasma glucose target [3.9–4.9 mmol/l (70–89 mg/dl)]. Results: IDegAsp once daily was non‐inferior to IGlar once daily in reducing HbA1c after 26 weeks [mean estimated treatment difference IDegAsp once daily − IGlar once daily: −0.03% (95% CI −0.20, 0.14)]. The evening meal glucose increment was significantly lower with IDegAsp once daily vs IGlar once daily [estimated treatment difference IDegAsp once daily − IGlar once daily: −1.32 mmol/l (95% CI −1.93, −0.72); P < 0.05]. The overall confirmed hypoglycaemia rate was higher with IDegAsp once daily (estimated rate ratio 1.43; 95% CI 1.07, 1.92; P < 0.05). The rate of nocturnal hypoglycaemia did not significantly differ between the IDegAsp and IGlar groups [estimated rate ratio 0.80 (95% CI 0.49, 1.30); not significant]. Conclusions: In participants with Type 2 diabetes inadequately controlled on basal insulin, IDegAsp once daily improved glycaemic control and was non‐inferior to IGlar once daily. IDegAsp led to higher rates of overall hypoglycaemia than IGlar, with no significant difference in rates of nocturnal hypoglycaemia. What's new?: After 26 weeks, treatment with insulin degludec/insulin aspart (IDegAsp) once daily effectively improved glycaemic control and was non‐inferior to insulin glargine (IGlar) once daily in terms of lowering HbA1c in participants with Type 2 diabetes inadequately controlled on basal insulin. Compared with IGlar, higher rates of overall hypoglycaemia were observed with IDegAsp, primarily in relation to the meal at which it was dosed (IDegAsp was administered once daily at the same fixed meal every day). The possibility of using IDegAsp once daily offers flexibility in the injection and provides both specific mealtime coverage and the benefits of full 24‐h basal coverage in a single injection.